Deciphering the Assembly of Enveloped Viruses Using Model Lipid Membranes - Erwan Brémaud; Cyril Favard; Delphine Muriaux (Membranes, 2022)
The cell plasma membrane is mainly composed of phospholipids, cholesterol and embedded proteins, presenting a complex interface with the environment. It maintains a barrier to control matter fluxes between the cell cytosol and its outer environment. Enveloped viruses are also surrounded by a lipidic membrane derived from the host-cell membrane and acquired while exiting the host cell during the assembly and budding steps of their viral cycle. Thus, model membranes composed of selected lipid mixtures mimicking plasma membrane properties are the tools of choice and were used to decipher the first step in the assembly of enveloped viruses. Amongst these viruses, we choose to report the three most frequently studied viruses responsible for lethal human diseases, i.e., Human Immunodeficiency Type 1 (HIV-1), Influenza A Virus (IAV) and Ebola Virus (EBOV), which assemble at the host-cell plasma membrane. Here, we review how model membranes such as Langmuir monolayers, bicelles, large and small unilamellar vesicles (LUVs and SUVs), supported lipid bilayers (SLBs), tethered-bilayer lipid membranes (tBLM) and giant unilamellar vesicles (GUVs) contribute to the understanding of viral assembly mechanisms and dynamics using biophysical approaches.